PERAN KELUARGA DALAM MEMBENTUK KARAKTER ISLAMI ANAK DI DESA PAKUNIRAN - Afif Zamroni; Ahmad Fauzi; Mohammad Solihin (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the role of families in shaping children's Islamic character in Pakuniran Village. The approach used in this study was descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of parents, school-age children, and local community and religious leaders. The results indicate that the role of families, especially parents, is significant in instilling Islamic values ​​through the practice of worship, moral education, and role models in daily life. Furthermore, support from the surrounding environment also contributes to strengthening children's Islamic character formation. Inhibiting factors identified include lack of time and technological challenges that influence parenting styles. Overall, this study emphasizes the importance of the active role of families in shaping children's Islamic character as a foundation for strengthening children's moral and spiritual well-being in the community.